Molecular Characterization of Chicken Anemia Virus (CAV) and Expression of the CAV VP3 Protein - Mohtar, Siti Hasmah (2003)
Chicken anemia virus (CAV) from non-attenuated and attenuated isolates were characterized based on sequence and phylogenetic analysis. The CAV BL-5 isolate, isolated from UPM was propagated and attenuated in MSB-1 cells until passage 90. The whole genome of non-attenuated isolate, BL-5P5 and attenuated isolate, BL-5P90 were amplified, cloned and subjected for sequencing. The sequences were analyzed and compared with other 25 isolates from local and foreign countries. Sequence analysis of VP1, VP2 and VP3 coding regions revealed that most of the variations were at the VP1 region. Sequence analysis of VP1 revealed that the BL-5P5 isolate was closely related to BL-5P90, CAF475 (China), AF313 (USA), C140 and A2 (Japan) and 3-1/P60 (Malaysia) isolates between 98% to 99% homology and distantly related to CAU269/7 (Australia) and SMSC-1 (Malaysia) isolates with 95% homology. However, analysis based on amino acid sequence indicated that the BL-5P5 isolate was closely related (98% to 99%) to all the above isolates, including the CAU269/7 isolate. It was found that the CAU269/7 has a very unusual low nonsynonymous/synonymous (NS/S) ratio of 0.188 when compared to the BL-5P5. Similarly, phylogenetic analysis based on the VP1 nucleotide sequences revealed that the BL-5P5 was closely related to BL-5P90, CAF475 (China) and AF313 (USA) and distantly related to CAU269/7 (Australia) and SMSC-1 (Malaysia) isolates . Analysis based on amino acid sequences revealed that the BL-5P5 was closely related to BL-5P90, CAU269/7 (Australia), Cf.F475 (China) and AF313 (USA) and distantly related to ConnB (USA), SMSC-1 (Malaysia) and P3102A9-resist isolates. The BL-5P90 showed only 15 nucleotide differences compared to BL-5P5 isolates. However, these differences associated with 11 amino acid changes which were found mainly in the hypervariable region of VP1. Thus, the NS/S ratio (2.75) is significantly higher than the SINS ratio (0.36). The BL-5P90 isolate has an amino acid substitution at position 144 from glutamic acid (E) to lysine (K) in VP1 hypervariable region. This amino acid substitution might play an important role in viral attenuation. The CAV VP3 gene from nonattenuated BL-5P5 isolate was expressed as a fusion protein in prokaryotic system. The SOS-PAGE and Western blot analysis indicated that the expressed VP3 protein of a pproximately 18 kOa was observed from the cell lysate sample after 4 hours post induction with isopropyl-I3-0-thiogalactosidase (IPTG). However, the protein was expressed in insoluble form and was relatively non-immunogenic since hyperimmune serum against the expressed protein showed non-specific reactions following Western blot and indirect immunofluorescence anti body test (IFAT) assay. Thus, the expressed VP3 protein in the present form is not suitable for use as antigen in production of antibody for the development of VP3 protein as diagnostic marker. Further studies on the application of the VP3 as diagnostic protein of CAV remains to be confirmed.